Internal Auditing Method within Public Institutions - A. L. Kolesnyk (Учёт. Анализ. Аудит, 2019)
In the process of public administration reform there has begun the implementation of modern international control and auditing standards in the public sector. The need for the improving of the efficiency of public administration requires the use of enhancement processes of public finance application and use, which in turn depends on the quality of feedback. The feedback was provided earlier by the control and auditing services, which were recording the cases of violation but at the same time, the evolution of the public internal financial control requires a shift in emphasis from the detection of violations to the analysis of the processes of the use of the resources. Not downplaying the importance of the elimination of these violations, the analysis of the main processes which involved the spending of budgetary funds, the identification of bottlenecks in such processes and introducing recommendations aimed at minimizing of the occurrence probability of adverse events is now the prevalent task of the modern state of the public internal auditing. Effective public internal auditing is designed to provide continuous assessment of the state internal control and it should help in the conditions of modern changing environment and regulatory shifts, by providing modern public administration. However, the liquidation or slow transformation in the process of reorganization of existing control structures, creates the risk of loss of the previously accumulated experience, as well as ineffective implementation of international standards of internal control and internal auditing, testifying to the fact of relevance growth of the research topic. This paper provides with the technique of internal auditing of state-owned institutions, which was developed on the basis of synergy works of domestic and foreign scholars and practitioners.